Лексико-тематическая группа глаголов речи и их дистрибуция - Н. Г. Брутян (Հայկական ԽՍՀ գիտությունների ակադեմիա)
Խոսքի բայերը լեզվի ամենագործուն բառաթեմատիկ շերտերից են։ Դրանք ուշագրավ են անփոփոխ և փոփոխական իմաստների հարաբերակցության (խոսակցական ակտի և խոսքի կոնկրետ բազմազան գործընթացների) տեսանկյունից։ Այդ բայերում տարբեր են հիմնական գործողության քանակական և որակական փոխակերպումները։ The speech verbs are one of the active lexical-thematic strata of the language. They are remarkable by virtue of interrelations of the invariable and variable meanings (the act of speech and the multiple speech processes). Quantitative and qualitative transformations of the basic action taking place within these verbs are different.
Keywords: Philology; Linguistics; Language and Literature